Restructuring the debt of farm operators - Kremer, Elżbieta (Przegląd Prawa Rolnego, 2021)
On 8 February 2019, the Act of 9 November 2018 on restructuring debts of entities running agricultural holdings entered into force. This law contains special solutions enabling partial settlement of debts taken up in relation to their agricultural activities. The reason for the introduction of special solutions was the increase in outstanding liabilities of farm operators towards the banks and financial institutions and the limited possibilities of farmers to restructure their debts under the existing provisions of the Act of 15 May 2015 – Restructuring Law. This Act contains, for the first time, a broad definition of the entities entitled to benefit from debt restructuring. That definition includes natural persons, legal persons, and organisational units without legal personality but with legal capacity, as well as small, medium-sized and large enterprises within the meaning of Annex I to the Commission Regulation (EU) No 702/2014. Debts that may be subject to restructuring are debts of monetary nature incurred in connection with an at least 3-year agricultural activity conducted by a farm operator who resides in Poland or whose registered office in the territory of the Republic of Poland, who is insolvent or threatened with insolvency.